Long-term outcomes after surgical repair of subvalvular aortic stenosis in pediatric patients - Schlein, Johanna; Wollmann, Felix; Kaider, Alexandra; Wiedemann, Dominik; Gabriel, Harald; Hornykewycz, Stephan; Base, Eva; Michel-Behnke, Ina; Laufer, Günther; Zimpfer, Daniel (Frontiers in Cardiovascular Medicine, 2022)
Objectives Subvalvular aortic stenosis (SAS) can occur as discrete or tunnel-like obstruction of the left ventricular outflow tract and as progressive disease often leads to aortic valve regurgitation. We report our 30-year single-center experience after surgical repair of SAS. Methods A retrospective chart review of all patients aged < 18 years, who underwent surgical repair of SAS from May 1985 to April 2020, was conducted. Mortality was cross-checked with the national health insurance database (93.8% complete mortality follow-up in April 2020). Survival and competing risks analysis were used to analyze the primary endpoints survival and incidence of reoperations. Results From May 1985 until April 2020 103 patients (median age 5.5 years) underwent surgical repair of SAS. Survival was 90.8% at 10 years and 88.7% at 20 and 30 years. Age < 1 year at time of surgery, Shone’s complex, mitral stenosis and concomitant mitral valve surgery were associated with mortality. The cumulative incidence of reoperation for SAS was 21.6% at 10 years, 28.2% at 20 and 30 years. The incidence of reoperation for SAS did not differ between the myectomy, membrane resection and combined myectomy and membrane resection groups. The cumulative incidence of reoperation on the aortic valve was 13.5% at 20 years. Conclusion Recurrence rate of SAS is not to be neglected, though surgical repair of subaortic stenosis has good long-term results. Patients who needed a combined membrane resection and septal myectomy are not more prone to recurrence than patients who underwent solitaire myectomy or membrane resection.